Experimental and Numerical Investigations of Air Cooling for a Large-Scale Motor - Chih-Chung Chang; Chiao-Hung Cheng; Ming-Tsun Ke; Sih-Li Chen (International Journal of Rotating Machinery)
This article experimentally and numerically investigates the thermal performance of a 2350-kW completely enclosed motor, which is cooled through an air-to-air heat exchanger. The air in the heat exchanger includes external and internal flow paths. The external air driven by the rotation of the centrifugal fan goes through the heat exchanger mounted on the top of the frame. The internal air absorbs heat released from the stator and the rotor and then transfers the heat to the heat exchanger through the motion of two axial fans and the rotor. Several test rigs have been set up to measure the performance of the fan and the motor. The Fluent software package is adopted to analyze the complicated thermal-fluid interactions among the centrifugal fan, two axial fans, heat exchanger, stator, and rotor. The measured data, including the fan performance curves and the temperature profiles of the heat exchanger and the stator, show good agreement with the simulated results. The numerical calculations also show that the nonuniform external flow distribution through the heat exchanger and the air leakage between the axial fan and the rotor reduces the cooling ability of the motor. A detailed discussion is also included to improve the motor cooling performance.